Gabinete do ódio e fake news – os métodos da extrema-direita e a corrosão da democracia no Brasil - Negreiros, Célia Rejane Araújo (2022)
This paper deals with the impact of fake news and misinformation on the 2018 presidential election in Brazil and the first two years of The Government of Jair Messias Bolsonaro, as well as the elements of dedemocratization as a symptom of the advance of ultraliberalism, neoconservatism and religious fundamentalism. It seeks to point out how the organization of new rights contributed to the rise of bolsonarism, its origins, language and relationship with a sour propaganda machine to spread hatred, chaos, attack the political system, democratic institutions and democracy. It also seeks to discuss the creation of the so-called Office of Hatred as a fascist strategy of democratic corrosion. Investigated by the CPMI of Fake News and the Supreme Court (STF), this digital militia based in the Planalto Palace, was financed with public money as also denounced by the press. This work is qualitative. Bibliographic and documentary sources were used for its elaboration.